Some Convergence Theorems of Three-Step Iteration for G-Nonexpansive Mappings on Banach Spaces with Graph - Team, Support (Thai Journal of Mathematics, 2018)
In this paper, the authors prove weak and strong convergence of a sequence {x_n} generated by a three-step iteration, to some common ﬁxed points of three G-nonexpansive mappings deﬁned on a Banach space endowed with a graph.